ORGANIZATIONAL COMMITMENT IN THE WAQF ORGANIZATION OF MUHAMMADIYAH: A Perspective From Social Exchange Theory - Moh Rifqi Khairul Umam (AL-TAHRIR, 2020)
Abstract: Organizational commitment is a critical element in achieving organizational goals. The theory of social exchange can explain the causes of organizational commitment by proposing leader-member exchange (LMX) and perceived organizational support (POS) as antecedents. However, most of the research has only been applied to proft organizations and has not touched many non-proft organizations. Muhammadiyah, as one of the representatives of the largest waqf manager in Indonesia, was chosen as the object of this study, where the waqf offcials in the Muhammadiyah environment of the Yogyakarta Special Region (DIY) were used as respondents. The results of this study indicate that LMX does not have a signifcant inﬂuence in forming organizational commitment directly, but has an indirect effect on organizational commitment through POS while showing the inability of POS to be a moderator variable in the relationship between LMX and organizational commitment. The new fnding of this research is that LMX requires POS mediation in inﬂuencing organizational commitment, especially in the context of the nonproft organization.